Nrf2 Signaling Modulates Cigarette Smoke Induced Complement Activation in Retinal Pigmented Epithelial Cells - Wang, Lei (2014)
While cigarette smoking (CS) and dysregulated complement are thought to play a central role in age-related macular degeneration (AMD), their exact roles are unknown. The aim of this study is to determine if CS activates complement and if the antioxidant transcription factor Nrf2 modulates this response. In AMD specimens, Nrf2 immunolabeling was strong in the cytoplasm with scattered nuclear labeling of macular retinal pigmented epithelial (RPE) cells that appeared normal, but was decreased and without nuclear labeling in dysmorphic cells overlying drusen, a hallmark AMD lesion. Cigarette smoke extract (CSE) induced Nrf2 nuclear translocation in RPE cells with increased antioxidant and complement gene expression. While CFH protein was not altered by CSE, cell membrane regulator proteins CD46, CD55, and CD59 were decreased, while C3a and C3b, but not iC3b, were increased compared to controls. C5b-9 was increased by CSE, but at sublytic levels only after addition of normal human serum. Nrf2-knockdown enhanced the increase of C3a and C3b from CSE, but not iC3b, C5a, or C5b-9. CSE also increased IL-1b expression and secretion after C3a generation, and was reduced by a C3aR antagonist. In contrast, the Nrf2 activator CDDO-Im restored complement gene expression in RPE cells exposed to CSE. We provide evidence of altered Nrf2 in human AMD, and that CSE induces a pro-inflammatory environment specifically by generating C3a and C3b, and Nrf2 deficiency magnifies this specific complement response.